2021
DOI: 10.1123/iscj.2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Technology in Football Coaching: Barriers and Opportunities

Abstract: Virtual reality (VR) technology has the potential to become the next performance measure in coaching by enhancing players’ perceptual ability. This paper aims to analyze elite coaches’ and performance analysts’ perceptions of barriers to and opportunities for the adaptation of VR technology in football coaching. Following a pilot study, interviews were conducted with six elite coaches and performance analysts. Perceptions of the key barriers to VR’s widespread adoption were the following: lack of conclusive ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…virtual reality, 2D reality etc) to assess key cognitive attributes such as decision making in soccer are limited [ 6 ]. Despite limited research, the application of virtual reality (VR) in professional sport is becoming increasingly common [ 7 ], largely due to it becoming more commercially available [ 8 ]. Virtual reality is defined as a computer-simulated environment that aims to induce a sense of being mentally and/or physically present in another place [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…virtual reality, 2D reality etc) to assess key cognitive attributes such as decision making in soccer are limited [ 6 ]. Despite limited research, the application of virtual reality (VR) in professional sport is becoming increasingly common [ 7 ], largely due to it becoming more commercially available [ 8 ]. Virtual reality is defined as a computer-simulated environment that aims to induce a sense of being mentally and/or physically present in another place [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, only one study has explored the perceptions of VR use in professional soccer. Thatcher et al [ 8 ] identified key opportunities for VR implementation including its use during rehabilitation and for youth development, as well as barriers to its use, such as a lack of empirical evidence and the practicality of using it. However, the opinions of soccer coaches interviewed by Thatcher et al [ 8 ] varied markedly on the efficacy of VR, and more importantly the aims of the study did not address the mechanistic factors that influence coaches’ intentions to use the technology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has also been suggested that target activation and distractor inhibition may occur in parallel during tracking and that this attentional allocation feature is primarily related to task difficulty and varies flexibly with task demands (tracking load) [20]. When task difficulty is low, visual attention is not necessary for tracking task completion, but increasing task difficulty leads to competition for attention in both tracking and detection tasks.…”
Section: Related Workmentioning
confidence: 99%